Quantifying primary oxidation products in the OH-initiated reaction of benzyl alcohol - R. S. Buenconsejo; S. M. Charan; J. H. Seinfeld; J. H. Seinfeld; P. O. Wennberg; P. O. Wennberg (Atmospheric Chemistry and Physics)
Benzyl alcohol is found in many volatile chemical products (VCPs) including a number of personal care products and industrial solvents. We report here on the products of the gas-phase oxidation of benzyl alcohol by OH and its dependence on nitric oxide (NO) levels. Using a gas chromatography in tandem with a chemical ionization mass spectrometer (CIMS) and gas chromatographer with a flame ionization detector (GC-FID), we measure the branching fractions to the major gas-phase oxidation products: hydroxybenzyl alcohol (HBA) and benzaldehyde. Later-generation oxidation products from both HBA and benzaldehyde pathways are also observed. In particular, catechol is a major gas-phase product of HBA. The fraction of H abstraction from benzyl alcohol leading to benzaldehyde formation is unaffected by [NO], with an average branching fraction of (21±10) %. The fraction of OH addition leading to HBA formation (36±18) % also does not appear to vary with [NO]. Consistent with the known high SOA yields of catechol, we find that HBA has a very high secondary organic aerosol (SOA) yield. Thus, benzyl alcohol and its oxidation products efficiently produce secondary organic aerosol – under some conditions approaching unity. Insights from the present study can help elucidate the chemistry of other atmospherically relevant aromatic compounds, especially those found in VCPs.